2018
DOI: 10.2139/ssrn.3149887
|View full text |Cite
|
Sign up to set email alerts
|

Does Deforestation Increase Malaria Prevalence? Evidence from Satellite Data and Health Surveys

Abstract: Deforestation has been found to increase malaria risk in some settings, while a growing number of studies have found that deforestation increases malaria prevalence in humans, suggesting that in some cases forest conservation might belong in a portfolio of anti-malarial interventions. However, previous studies of deforestation and malaria prevalence were based on a small number of countries and observations, commonly using cross-sectional analyses of less-than-ideal forest data at the aggregate jurisdictional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The importance of addressing complex confounding structures influencing the relationship between deforestation and malaria was also highlighted by Bauhoff and Busch, 2020 . Variables such as temperature ( Beck-Johnson et al, 2013 ; Mordecai et al, 2013 ), precipitation ( Parham and Michael, 2010 ; Parham et al, 2012 ), or seasonality Hay et al, 1998 are known environmental predictors of malaria, although the spatio-temporal scale of those effects often varies across different areas ( Teklehaimanot et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of addressing complex confounding structures influencing the relationship between deforestation and malaria was also highlighted by Bauhoff and Busch, 2020 . Variables such as temperature ( Beck-Johnson et al, 2013 ; Mordecai et al, 2013 ), precipitation ( Parham and Michael, 2010 ; Parham et al, 2012 ), or seasonality Hay et al, 1998 are known environmental predictors of malaria, although the spatio-temporal scale of those effects often varies across different areas ( Teklehaimanot et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“… Bauhoff and Busch, 2020 identified only 10 empirical studies that assessed the relationship between deforestation and malaria with appropriate adjustments for confounding. Of these, seven reported a positive association ( Austin et al, 2017 ; Wayant et al, 2010 ; Olson et al, 2010 ; Terrazas et al, 2015 ; Pattanayak et al, 2010 ; Garg, 2015 ; Fornace et al, 2016 ), two did not find any associations ( Bauhoff and Busch, 2020 ; Hahn et al, 2014a ), and one disputed study found a negative association ( Valle and Clark, 2013 ; Hahn et al, 2014b ; Valle, 2014 ). Most recently, a study found deforestation to increase malaria risk and malaria to decrease deforestation activities in the Amazon, using an instrumental variable analysis to disentangle any reverse causality loop ( MacDonald and Mordecai, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Deforestation in particular has received increased attention in recent years and is hypothesized to operate through changes to the physical environment, malarial mosquito biology, and human exposure (15). While most have found that deforestation is associated with increased malaria incidence (16), this result does not hold across all regions and study designs (17). However, linkages between malarial dynamics and ecosystem disruption by invasive species has not been previously studied, aside from well-known linkages to invasive mosquito vectors.…”
Section: Figmentioning
confidence: 96%
“…The importance of addressing complex confounding structures influencing the relationship between deforestation and malaria was highlighted by Bauhoff et al [12]. Variables such as temperature [13, 44], precipitation [51, 50] or seasonality [35] are known environmental predictors of malaria, although the spatio-temporal scale of those effects if often highly variable across different areas [59].…”
Section: Introductionmentioning
confidence: 99%
“…Bauhoff et al [12] identified only 10 empirical studies that assessed the relationship between deforestation and malaria with appropriate adjustments for confounding. Of these, seven reported a positive association [10, 67, 48, 60, 53, 27, 25], two did not find any associations [12, 31], and one disputed study found a negative association [64, 32, 63]. Most recently, a study found deforestation to increase malaria risk and malaria to decrease deforestation activities in the Amazon, using an instrumental variable analysis to disentangle any reverse causality loop [43].…”
Section: Introductionmentioning
confidence: 99%